Exploring the determinants of thyroid disorders in high-altitude western Himalaya: a geospatial and epidemiological study - Arshad Ahmed; Kheraj; Alireza Mohammadi; Robert Bergquist (Journal of Health, Population and Nutrition)
Abstract Background The impact of high-altitude on thyroid function is an emerging field of research. Apart from environmental stress through hypoxia and iodine deficiency, socioeconomic, demographic, and dietary factors may play a role, particularly for those with pre-existing thyroid conditions. This study explored the prevalence and determinants of thyroid disorders (TDs) among the Gujjar and Bakarwal tribes in the high-altitude western Himalayas. Methods We assessed potential risk factors, with focus on environment, socioeconomy and lifestyle based on household survey data. A stratified random sampling method was employed to select a representative sample (n = 816) from 50 villages. The binary logistic regression model (BLRM) was used to identify risk factors for TDs, with model fit evaluated using pseudo-R2 and Hosmer–Lemeshow tests. Geographic information systems were utilized to map the spatial distribution of thyroid disorder prevalence, and the model’s predictive accuracy was validated using receiver operating characteristic (ROC). Results The TD prevalence was 18.6%. Higher altitude significantly increased likelihood of this disease (adjusted odds ratio [AOR]: 6.80, 95% CI: 1.62–28.50, p = 0.009). The Bakarwals had lower odds compared to the Gujjars (AOR: 0.19, 95% CI: 0.05–0.67, p = 0.010). Risk factors included living in extended families, smoking, other tobacco uses, traditional housing and specific dietary patterns. Protective factors included modern housing, higher education and iodized salt consumption. High-risk areas were concentrated to middle and high-altitude zones. The model demonstrated excellent fit (Hosmer–Lemeshow, p = 0.967, Nagelkerke R2 = 90.5) and high predictive accuracy (ROC-AUC = 0.99). Conclusion Thyroid disorders in this high-altitude population are influenced by a combination of environmental, demographic, and lifestyle factors. This study underscores the need for tailored public health interventions that address these determinants and reduce health disparities in geographically challenging regions. Future research should explore these findings in other high-altitude contexts to guide global thyroid health strategies.